Sintesis Etil Sinamat dari Sinamaldehid pada Minyak Kayu Manis (Cinnamomum cassia) dan Uji Aktivitas sebagai Antidiabetes - Amalia, Dian; , S.Si., M.Si., Ngadiwiyana; Fachriyah, M.Si, Dra. Enny (Chem Info Journal, 2013)
Cinnamon oil is obtained by distillation from the bark of cinnamon. The main component in cinnamon oil is cynnamaldehyde (42-75%). Cynnamaldehyde is a compounds which has aldehyde group that can be modified into the ester group that can be used as an antidiabetic. The synthesis cinnamic esters was oxidation and esterification. This research aims to isolate cynnamaldehyde of cinnamon oil, synthesized cinnamic acid and activities test as antidiabetic. Ethyl cinnamic is obtained from the synthesis of a clear yellow liquid and fragrant with a yield 98.86%. The results of FTIR showed the formation of cinnamic ethyl ester in the presence of CO groups, where as the results obtained by GC-MS abudance of 99.01% ethyl cinnamate. From the antidiabetic test results, ethyl cinnamate coumpounds IC50 values of 215.509 ppm.